Ghosts of transparency — shadows cast and shadows cast out (2019)
Code. Protocol. Channel. Data. Information. In everyday conversations, these words do not evoke images of buildings or of cities. And yet they have entered the common parlance of an architecture and urbanism looking to computation and quantum physics for inspiration. As the net is cast wider and other disciplines and fields are probed for concepts and theories, new words are gathered and circulated: Entropy. Negentropy. Isotropy. Anisotropy. Spectrum. Manifold. These words are appropri- ated and articulated into novel constellations of meaningfulness, as well as meaninglessness respectively.